Phosphorus bioavailability in diets for growing horses - Oliveira, A. A. M. A.; Furtado, C. E.; Vitti, D. M. S. S.; Resende, F. D.; Cabral Filho, S. L. S.; Tosi, H. [UNESP]; Winkler, B. (Elsevier B.V., 2008)
A study of phosphorus (P) metabolism was carried out using 12 month old Brasileiro de Hipismo breed of horses to determine the P bioavailability available from feeds commonly fed to horses in Brazil. Five different diets were formulated to contain approximately equivalent levels of crude protein and digestible energy, as well as to supply at least 22 g P/horse/day (NRC, 1989). All 5 diets contained 40% Bermuda coastal hay plus 60% concentrate. The 5 different concentrates contained: C1 (corn+ cottonseed meal) C2 (corn grain+soybean meal) C3 (corn+sugarcane yeast), C4 (oat+cottonseed meal), and C5 (oat+soybean meal). The radioisotope (32)p was injected with 30 NIB. Blood, feces and urine were collected for 7 days to evaluate endogenous fecal P and true absorption. Analysis of variance of P intake showed differences due to dietary effects (P < 0.05). Concentrate C3 had the lowest intake (79.68 mg/ kg BW). All of the diets produced positive P retention. Absolute values for P concentrations in plasma, urine, feces and endogenous feces did not vary between diets. Values for endogenous fecal P were independent of the level of P intake, so the correlation between P intake and P endogenous was not significant. P bioavailability values were 50.75; 40.98; 43.50; 51.03 and 57.68% for diets C1 through C5, respectively. However, differences in P bioavailability were found (P < 0.05) between diets. Diets C2 and C3 had lower P bioavailability than the other diets. The P bioavailability of all dietary treatments in this study exceeded NRC (1989) postulations of 35% true P absorption in diets not supplemented with inorganic P. The results of this study indicate that inorganic P supplementation is not needed for growing yearlings fed common Brazilian feeds. Considering the high cost of P supplementation and the risk of environmental P contamination, inorganic phosphorus supplementation for growing yearlings may not be required. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Phosphorus; bioavailability; Equine; true absorption